2007
DOI: 10.1371/journal.pbio.0050203
|View full text |Cite|
|
Sign up to set email alerts
|

Targeted Inhibition of miRNA Maturation with Morpholinos Reveals a Role for miR-375 in Pancreatic Islet Development

Abstract: Several vertebrate microRNAs (miRNAs) have been implicated in cellular processes such as muscle differentiation, synapse function, and insulin secretion. In addition, analysis of Dicer null mutants has shown that miRNAs play a role in tissue morphogenesis. Nonetheless, only a few loss-of-function phenotypes for individual miRNAs have been described to date. Here, we introduce a quick and versatile method to interfere with miRNA function during zebrafish embryonic development. Morpholino oligonucleotides target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
348
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(356 citation statements)
references
References 39 publications
5
348
0
3
Order By: Relevance
“…These mice display hyperglycaemia and hyperglucagonaemia and, if crossed with ob/ob mice, a model of obesity and insulin resistance, they develop a severe diabetic state because of the inability of beta cells to expand and compensate for the increased insulin needs. These, together with other studies [16][17][18][19], highlight the central role played by miR-375 in endocrine pancreas development and in the regulation of insulin gene expression and release.…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funsupporting
confidence: 59%
“…These mice display hyperglycaemia and hyperglucagonaemia and, if crossed with ob/ob mice, a model of obesity and insulin resistance, they develop a severe diabetic state because of the inability of beta cells to expand and compensate for the increased insulin needs. These, together with other studies [16][17][18][19], highlight the central role played by miR-375 in endocrine pancreas development and in the regulation of insulin gene expression and release.…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funsupporting
confidence: 59%
“…MiR-375 gene knockout mice revealed that miR-375 is not only required for normal glucose homeostasis but also influences pancreatic α-and β-cell mass [24]. Inhibition of miR-375 maturation with morpholinos in zebrafish has revealed an essential role for miR-375 in the formation of insulin-secreting pancreatic islet [25]. By far, functional studies of miR-375 appear to be restricted to the regulation of pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…S1). The increased rate of regeneration at this temperature allows disruption of gene function by morpholinos, which can persist for up to 72 h (31). Because the array data were obtained from fish maintained at 27°C, we first verified, by northern blot analysis, that the patterns of expression for differentially expressed miRNAs, as determined using arrays, were similarly altered when regeneration proceeded at 33°C Microarrays were performed to identify differentially expressed miRNAs during caudal fin regeneration.…”
Section: Lef1 ͉ Mir-203mentioning
confidence: 99%
“…2B). We also co-injected antisense morpholinos complementary to miR-203 (i.e., miR-203 MO ) that function to block the activity of endogenous miR-203 and thus should lead to increased fluorescence (31,33). As a control, GFP lacking the lef1 3Ј UTR also was injected into single-cell zebrafish embryos with and without exogenous miR-203 and miR-203 MO (Fig.…”
Section: Figmentioning
confidence: 99%